Natural Treatments for Fissure in Ano Used by Traditional Persian Scholars, Razi (Rhazes) and Ibn Sina (Avicenna) - Ali Reza Derakhshan MD, PhDc (SAGE Publishing, 2017)
Most cases of chronic fissure do not respond to medical treatment. Razi and Ibn Sina were 2 of the best-known scientists of ancient Persia. The purpose of this study was to find out new scientific evidence in modern medicine about their recommendations, in order to find certain clues to conduct useful researches in the future. First, treatments of anal fissure mentioned by Razi and Ibn Sina were reviewed. Then, literature search was made in electronic databases including PubMed, Scopus, and Google Scholar. Management of anal fissure according to Razi's and Ibn Sina's practices is done based on 3 interventions: lifestyle modifications, drug treatments, and manual procedures. Almost all remedies suggested by Razi and Ibn Sina have shown their effects on fissure in ano via several mechanisms of action in many in vitro and in vivo studies; Still there is lack of human studies on the subject.